Activating α7 nicotinic acetylcholine receptor inhibits NLRP3 inflammasome through regulation of β‐arrestin‐1. (21st September 2017) - Ke, Ping; Shao, Bo‐Zong; Xu, Zhe‐Qi; Chen, Xiong‐Wen; Wei, Wei; Liu, Chong
Summary: Aims: To evaluate whether activating α7 nicotinic acetylcholine receptor (α7nAChR) could inhibit the NOD‐like receptor family, pyrin domain containing 3 (NLRP3) inflammasome through regulation of β‐arrestin‐1 in monocyte/macrophage system, thus contributing to the control of neuroinflammation. Methods: The protein levels of NLRP3, caspase‐1 (Casp‐1) p20 and proCasp‐1, interleukin‐1β (IL‐1β) p17 and proIL‐1β, IL‐18 and proIL‐18 were measured using Western blotting. The mRNA levels of Casp‐1 and IL‐1β were detected by real‐time PCR (RT‐PCR). The colocalization and interaction of NLRP3 protein and β‐arrestin‐1 were measured by immunofluorescence staining and immunoprecipitation. Results: The expression of β‐arrestin‐1 was significantly increased and colocalized with CD45‐positive cells in spinal cord of experimental auto‐immune encephalomyelitis (EAE) mice when compared with the sham mice, which was attenuated by pretreatment with PNU282987, a specific α7nAChR agonist. PNU282987 also significantly inhibited the activation of NLRP3 inflammasome and thus decreased the production of IL‐1β and IL‐18 both in lipopolysaccharide (LPS)/ATP‐stimulated BV2 microglia in vitro and spinal cord from EAE mice in vivo, while inverse effects were observed in α7nAChR knockout mice. Furthermore, overexpression of β‐arrestin‐1 attenuated the inhibitory effect of PNU282987 on NLRP3 inflammasome activation in LPS/ATP‐stimulated BV2 microglia. PNU282987 inhibited the interaction between β‐arrestin‐1 and NLRP3 protein in vitro. Conclusions: The present study demonstrates that activating α7nAChR can lead to NLRP3 inflammasome inhibition via regulation of β‐arrestin‐1 in monocyte/microglia system.